FAKTOR-FAKTOR YANG MEMENGARUHI PARTISIPASI MASYARAKAT DALAM PENGANGGARAN DAN PENDAPATAN ASLI DESA - Zaenal Fanani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2018)
The purpose of this study was to examine the influence of village characteristics factors, leadership styles, political legitimacy, access to information, and village head motivation on community participation in village budgeting and to examine the effect of community participation in budgeting on village original revenues. The population of this study is the village head of all villages in East Java Province, the sample is 100 village heads. Data analysis techniques used to test the hypothesis using Structural Equation Modeling (SEM) with software Wrap-PLS 5.0. The result of the research shows that the factor of political legitimacy influences the motivation of village head, the character of the village influences the participation of the society in budgeting in the village. Factors of leadership style, political legitimacy, and access to information, have no effect on the village head's motivation. Factors of leadership style, political legitimacy, and access to information, and the motivation of village heads do not influence public participation in village budgeting. Public participation in budgeting has an effect on the original income of the village.